Enriching tuberculosis research by measuring poverty better: a perspective - Chelsie Cintron; Madolyn Rose Dauphinais; Xinyi Du; Alexa Tabackman; Andrew Lenart; Ashley Laliberte; Jakob Dirksen; Pranay Sinha (BMC Global and Public Health)
Abstract The relationship between poverty and tuberculosis (TB) is well-documented, as socio-economic deprivation constitutes a risk factor that drives TB transmission and progression while hindering treatment adherence. Despite the importance of controlling for socio-economic status (SES) in TB research, no universally accepted tool exists to measure multidimensional poverty’s impact on TB-affected households. This article provides an overview of existing SES assessment tools, including income-based measures, wealth indices like the Demographic and Health Survey (DHS) and the International Wealth Index (IWI), and multidimensional indices, such as the global Multidimensional Poverty Index (MPI). Each method’s strengths and limitations are considered, particularly in light of the complex deprivations relevant to TB. Recognizing the distinct SES determinants of TB, we emphasize the need for multidimensional, standardized SES measures that are contextually relevant and feasible for TB epidemiology, programmatic evaluations, and translational research. By advancing poverty metrics in TB studies, the global community can better address socio-economic drivers of TB and prioritize pro-poor interventions, fostering equitable health outcomes.